Effect of Ti particles on the LPSO phase and mechanical properties of TiP/VW94 composites - Dongmei Pu; Xianhua Chen; Jingfeng Wang; Jun Tan; Jianbo Li; Hong Yang; Bo Feng; Kaihong Zheng; Fusheng Pan (Journal of Materials Research and Technology, 2023)
For magnesium matrix composites (MMCs), it is crucial to enhance their strength while maintaining plasticity. In this work, Ti particle (TiP) reinforced VW94 composites (TiP/VW94 composites) with varying amounts of Ti particles were prepared using a semi-solid stirring-assisted ultrasonic vibration method followed by homogenizing treatment. Microstructural analysis revealed that the addition of Ti particles resulted in grain refinement and facilitated the formation of lamellar long period stacking ordered structure (LPSO) during homogenizing treatment due to the increasing dislocation density. In addition, the jagged interfacial product of MnTi phase was generated at the interface between Ti particles and Mg matrix, and a strong interfacial bonding was formed at the Mg/Ti interface. The tensile test results show that the strength and elongation of TiP/VW94 composites all improved than VW94 matrix alloy and the 5%TiP/VW94 composite presents the best tensile properties with yield strength (YS), ultimate tensile strength (UTS), and elongation of 173 MPa, 256 MPa and 5.9%, respectively. The improved tensile properties of TiP/VW94 composites can be attributed to grain refinement, load transfer, dispersion strengthening, dislocation strengthening, and an increase in lamellar LPSO.